Емпатія як складова комунікативних компетентностей студента-медика - Кизима, Наталя Володимирівна (My University, 2018)
У медичній сфері спілкування між пацієнтом і лікарем є запорукою досягнення позитивного результату діагностики та лікування, поваги пацієнтів та популярності серед них. Однією з важливих характеристик міжособистісного розуміння і взаємодії є емпатія. Шляхом тестування визначено «високий» рівень емоційного відгуку у студентів медичного факультету за методикою А. Меграбяна, Н. Епштейна. Empathy in formation of medical student communicative competencies. The communication between patient and physician is the key to achieving a positive result of diagnosis and treatment, patient respect and popularity among them in the medical field. One of the most important characteristics of interpersonal understanding and interaction is empathy. By means of testing, the "high" level of emotional response was determined by the students of the medical faculty according to A. Megrabyan, N. Epstein's method.
Keywords: спілкування; комунікація; лікар; пацієнт; емпатія; communication; physician; patient; empathy; understanding